P118 Pentraxin-3 interacts with Aspergillus fumigatus conidia to regulate pro-inflammatory cytokine production. (20th September 2022) - Dellière, Sarah; Wong, Sarah; Chauvin, Camille; Bayry, Jagadeesh; Carvalho, Agostinho; Inforzato, Antonio; Aimanianda, Vishukumar
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Objectives: Long pentraxin-3 (PTX3) is a soluble pattern-recognition receptor secreted by phagocytes and non-immune cells at sites of inflammation. It has been reported to have a nonredundant role in the immune response against Aspergillus fumigatus . Indeed, PTX3 knock-out mice show an increased susceptibility to invasive pulmonary aspergillosis (IPA) with a higher mortality rate. In humans, PTX3 genetic deficiency or single nucleotide polymorphism has also been associated with an increased risk of IPA. However, the way in which PTX3 interacts with A. fumigatus and its mechanism of action has yet to be elucidated. The aim of the study was to investigate potential A. fumigatus ligands for PTX3 and the impact of A. fumigatus opsonization by PTX3 on modulating the immune response. Methods: Aspergillus fumigatus conidia, the infective morphotype, were incubated with PTX3 with or without human serum, stained with anti-PTX3 antibody, and studied by immunofluorescence. Identification of potential fungal ligands for PTX3 was performed by ELIS A. Fixed conidia and germinated conidia were opsonized with different serum factors and co-incubated with human monocyte-derived macrophages (hMDM) for 24 h at 37°C. Culture supernatants were collected, and pro-/anti-inflammatory cytokines were measured by sandwich ELISA. Results: PTX3 did not bind A. fumigatus conidia directly but in the presence of human serum, purified collectins [surfactant protein D (SP-D) or C1q], and complement products (C3b). Pre-opsonization of conidia with these complement proteins or SP-D stimulated proinflammatory cytokine secretion by hMDM upon interaction (Fig. 1a). In contrast, secondary opsonization of complement proteins or SP-D opsonized conidia with PTX3 significantly reduced pro-inflammatory cytokines and increased anti-inflammatory cytokine secretion from hMDM. PTX3 opsonized PFA-fixed germinating conidia significantly reduced pro-inflammatory cytokine and increased anti-inflammatory cytokines secretion from hMDM (Fig. 1b). Conclusion: PTX3 is an acute phase protein expressed in response to pro-inflammatory stimuli during infection and that is increased in bronchoalveolar lavage of patients with aspergillosis. Our recent data with A. fumigatus suggest that PTX3 is an immunoregulatory protein that reduces pro-inflammatory response. Although an inflammatory response is necessary to fight against fungal pathogens, the tissue damage associated with enhanced inflammation can be deleterious and facilitate A. fumigatus infection.